Mapping Madurese Cultural Heritage for Secondary Science Education: An Ethnopedagogical Study in Sumenep, Indonesia - Dwi Swastanti Ridianingsih; Iis Nur Asyiah; Bevo Wahono; Sri Astutik; Imam Mudakir; Dwi Swastanti Ridianingsih; Iis Nur Asyiah; Bevo Wahono; Sri Astutik (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2027)
Science education increasingly requires contextual approaches that connect scientific concepts with students’ cultural experiences. However, local cultural knowledge is often underutilized as an educational resource, particularly in regions with rich cultural diversity such as Sumenep, Indonesia. Madurese cultural traditions contain various forms of ecological, technological, and social knowledge that remain insufficiently explored within science education. This study aims to identify Madurese cultural traditions in Sumenep and analyze their potential contribution to secondary science education through an ethnopedagogical perspective. The study focuses on mapping cultural practices, educational values, science-related knowledge, and potential learning approaches without claiming classroom effectiveness. A qualitative descriptive design was employed involving cultural exploration through semi-structured interviews, observations, and document analysis. Ten cultural informants were selected using purposive and snowball sampling techniques. Data were analyzed through thematic analysis to identify cultural themes, science-related phenomena, and preliminary ethnopedagogical connections. The findings identified thirteen Madurese cultural traditions categorized into five domains: ritual and belief systems, environmental and animal-related practices, traditional technology, performing arts, and social-cultural practices. These traditions contain educational values related to responsibility, cooperation, environmental awareness, and technological knowledge. The analysis revealed connections with secondary science concepts, including ecosystems, weather systems, biomechanics, materials science, heat transfer, and sound phenomena. A preliminary ethnopedagogical mapping framework was developed by connecting cultural traditions with potential inquiry-based, project-based, STEAM, and contextual learning approaches. This study demonstrates that Madurese cultural heritage can function as a valuable knowledge resource for culturally responsive science education. The proposed ethnopedagogical mapping provides an initial foundation for curriculum development and future classroom validation.